Regulation of platelet numbers and sizes by signaling pathways - Jaturawat Pawinwongchai; Ponthip Mekchay; Nungruthai Nilsri; Nipan Israsena; Ponlapat Rojnuckarin (Platelets, 2021)
Either the glycoprotein (GP) Ib deficiency or hyper-function in humans can cause macrothrombocytopenia, the molecular mechanisms of which remain unclear. Herein, the investigations for disease pathogenesis were performed in the human induced pluripotent stem cell (hiPSC) model. The hiPSCs carrying a gain-of-function GP1BA p.M255V mutation which was described in platelet-type von Willebrand disease (PT-VWD) were generated using CRISPR/Cas9. The GP1BA-null hiPSCs were previously derived from a Bernard–Soulier syndrome (BSS) patient. After full megakaryocyte differentiation in culture, both hiPSC mutations showed large proplatelet tips under fluorescence microscopy and yielded fewer but larger platelets compared with those of wild-type cells. The Capillary Western analyses revealed the lower ERK1/2 activation and higher MLC2 (Myosin light chain 2) phosphorylation in megakaryocytes with mutated GPIb. Adding a mitogen-activated protein kinase (MAPK) pathway inhibitor to wild-type hiPSCs recapitulated the phenotypes of GPIb mutations and increased MLC2 phosphorylation. Notably, a ROCK inhibitor which could inhibit MLC2 phosphorylation rescued the macrothrombocytopenia phenotypes of both GPIb alterations and wild-type hiPSCs with a MAPK inhibitor. In conclusion, the genetically modified hiPSCs can be used to model disorders of proplatelet formation. Both loss- and gain-of-function GPIb reduced MAPK/ERK activation but enhanced ROCK/MLC2 phosphorylation resulting in dysregulated platelet generation.